Faith, family, and friends as integral factors in student resilience in the Ateneo de Manila School of Science and Engineering - Chua, Queena Lee (2022)
What makes Filipino students resilient in times of crises, such as the COVID-19 pandemic? Even as some students succumb to anxiety and despair and lose motivation to learn, others actively take charge of their learning and remain hopeful and strong amid severe trials. What keeps them going, and what can we learn from them? 25 professors of the Ateneo de Manila School of Science and Engineering selected 92 college undergraduate and graduate students whom they observed to display resilience in learning and prodded them to reflect on how they overcame challenges in and out of the classroom. Whatever their circumstances, our study reveals that these resilient students rely on three main sources of support: deep faith, solid family bonds, and close friends and mentors who hold them accountable. As contrasted to the more individuals context that gives rise to resilience as posited by Western literature, Filipino resilience is instead truly a community affair.